DEVELOPING GRAMMAR INSTRUCTION USING THE ASSURE MODEL: A CASE OF TEACHING THE SIMPLE FUTURE TENSE - Nyanden, Kim David Jordan; Misrita, Misrita; Zulkarnain, Zulkarnain (Program Studi Magister Pendidikan Bahasa Inggris, Program Pascasarjana, Universitas Palangka Raya, 2024)
This study aimed to create an effective learning unit for teaching the simple future tense to 6th-grade students using the ASSURE instructional design model. The research followed the ASSURE model, involving the analysis of learners, stating clear instructional objectives, selecting appropriate methods, media, and materials, utilizing these materials effectively, requiring learner participation, and evaluating and revising the instructional process. It also incorporates strategies to actively engage learners and evaluates the outcomes for continuous improvement. For this research, a group of 15 students participated in interactive activities, including sentence construction and role-playing exercises. The evaluation process included pre-tests and post-tests, which showed substantial progress, with average scores rising from 52% to 80%. Both students and teachers provided feedback, praising the clarity and engagement of the materials, though minor adjustments were made to better address diverse learning needs. These findings highlight the effectiveness of the ASSURE model in designing practical, engaging, and impactful grammar instruction.